EFFECT OF GIVING FINANCIAL AND NON FINANCIAL COMPENSATION ON TEACHER PERFORMANCE IN MADRASAH ALIYAH NEGERI 1 (MAN1) BANDAR LAMPUNG SCHOOL - Prayogo Bayu Satyagraha (Prosiding International conference on Information Technology and Business (ICITB), 2018)
The success of school level education is very clear by the performance of the teacher. Each school will always strive to improve teacher performance in the hope of achieving school goals and educating students to be expected examples. Because there are several problems that arise, the numbers are decreasing in the number of teachers, some of the factors that cause are the factors that are unsatisfactory for teachers and nonfinancial compensation that is still in expectation. The purpose of this study was to measure financial performance and non-financial compensation for teacher performance at the Bandar Lampung Madrasah Aliyah 1 Bandar Lampung. The population in this study were 50 teachers and used saturated sampling. Data collection techniques using questionnaires and using multiple regression analysis methods, t test and f test, the results of the study consisting of financial and non financial financial data on teacher performance. Then the proper financial burden and the non-financial responsibilities obtained will affect the performance of the teachers of Madrasah Aliyah Negeri 1 Bandar Lampung.Keywords: Financial Compensation, Non Financial Compensation and Teacher Performance.